Hypertension in pregnancy - Bryce Moncloa, Alfonso (2018)
Hypertensive disorders during pregnancy are frequent complications considered an important cause of maternal and/or fetal morbidity and mortality. The various current guidelines on the management of hypertension during pregnancy agree to treat patients with blood pressure ≥ 160/105-110 mmHg due to a high risk of stroke, and to normalize the blood pressure to < 140/90 if there is end-organ damage. The evidence concludes that treatment of low to moderate hypertension reduces the risk to develop uncontrolled hypertension, but does not prevent preeclampsia. Regarding the choice of drug, none of the recommended agents is considered a first option because no data support either of them.